2019
DOI: 10.1002/adsc.201901549
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Catalytic Reductions Without External Hydrogen Gas: Broad Scope Hydrogenations with Tetrahydroxydiboron and a Tertiary Amine (Adv. Synth. Catal. 1/2020)

Abstract: The inside cover picture, designed by Lakshman and co‐workers, illustrates a diverse set of hydrogenations that can be conducted without use of external hydrogen gas (compressed gas). 4‐Methylmorpholine (NMM), tetrahydroxydiboron [B2(OH)4], and 5% Pd on charcoal work in concert to cause reductions of aryl halides and triflates, alkenes, alkynes, aldehydes, and azides, as well as cleavage of benzylic ethers and N‐Cbz groups. Based on the mechanistic knowledge gained in the study, aromatic deuteriations have als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…43,44 Typically, most hydrogen-rich boron hydrides (such as sodium borohydride, [45][46][47][48][49] ammonia borane, [50][51][52][53][54] and dimethylaminoborane [55][56][57][58][59] ) catalyzed by metal nanoparticles generate H 2 with only one H atom supplied by water and the other one by hydrogen-rich boron hydrides. Since 2020, our group successively reported highly efficient H 2 production upon water splitting at the expense of B 2 (OH) 4 (eqn (1)), which is a common borylation reagent [60][61][62][63][64][65][66][67][68] catalysed by acid, base or metal nanoparticles. 69,70 Experiments using D 2 O in place of H 2 O including the kinetic isotope effect and tandem reaction have confirmed that both H atoms of produced H 2 are only provided by water.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 Typically, most hydrogen-rich boron hydrides (such as sodium borohydride, [45][46][47][48][49] ammonia borane, [50][51][52][53][54] and dimethylaminoborane [55][56][57][58][59] ) catalyzed by metal nanoparticles generate H 2 with only one H atom supplied by water and the other one by hydrogen-rich boron hydrides. Since 2020, our group successively reported highly efficient H 2 production upon water splitting at the expense of B 2 (OH) 4 (eqn (1)), which is a common borylation reagent [60][61][62][63][64][65][66][67][68] catalysed by acid, base or metal nanoparticles. 69,70 Experiments using D 2 O in place of H 2 O including the kinetic isotope effect and tandem reaction have confirmed that both H atoms of produced H 2 are only provided by water.…”
Section: Introductionmentioning
confidence: 99%